Supra Rough Membership Relations and Supra Fuzzy Digraphs on Related Topologies - Sarmad, Samah; Yousif, Yousif Yaqoub (Iraqi Journal of Science, 2020)
The primary aim of this paper is to present two various standpoints to define generalized membership relations, and state the implication between them, in order to categorize the digraphs and assist for their gauge exactness and roughness. In addition, we define several kinds of fuzzy digraphs.